The Effects of Gallium Additions on Microstructures and Thermal and Mechanical Properties of Sn-9Zn Solder Alloys - Kang I. Chen; Shou C. Cheng; Chin H. Cheng; Sean Wu; Yeu-L. Jiang; Tsung-C. Cheng (Advances in Materials Science and Engineering)
The effects of gallium additions on microstructures and thermal and mechanical properties of the Sn-9Zn solder alloys are investigated in this study. The results show that the melting temperature of the alloys decreases with the increase in the Ga concentration, while the pasty ranges of the alloys are simultaneously enlarged. By adding a 0.25–0.5 wt.% Ga element, the Sn-matrix region is slightly increased and the Zn-rich phase becomes slightly coarser; however, the overall microstructure is still very similar to that of the Sn-9Zn alloy. It is found that, when the Ga concentration is less than 0.50 wt.%, the ultimate tensile strength and elongation are maintained at the same values. The addition of a 0.25–0.50 wt.% Ga to the Sn-9Zn alloy also leads to small cup and cone fracture surfaces which exhibit near-complete ductile fracturing. With the addition being increased to 0.75 wt.%, larger cup and cone fractures are observed. The 1.00 wt.% Ga alloy has lower strength and ductility due to the coarser and nonuniform microstructures. However, the fracture surfaces of the 1.00 wt.% Ga alloy show partial cleavage and a partially dimpled fracture.